Longevity and reproduction period of africanized queen bees in the Northeast region of Brazil - Gomes, Renata Valéria Regis de Sousa; Gramacho, Kátia Peres; Gonçalves, Lionel Segui (Medicina Veterinária, 2019)
This study aimed to evaluate the longevity and reproductive period of Africanized queen bees under the climatic conditions of the Zona da Mata region in the state of Pernambuco, Northeast of Brazil. Longevity and reproduction data of 41 Apis mellifera L. queen bees naturally fertilized were collected every 15 days from February 2014 to December 2015, and correlated with climatological data—precipitation, temperature, and relative humidity—from this period.  The mean longevity of the queen bees was 6.4±2.9 months. The months with the lowest number of death of queens were those with the highest precipitation—May to August—in the study region, presenting a strong negative correlation (r = -0.65 and p = 0.02) between the time of queen death and precipitation index. The peak of the reproductive season in this region was September to December. All queen bees laid eggs during all months of the year. The oviposition intensity of the queens and the number of brood combs increased as the temperature increased and the humidity and precipitation index decreased. A colony of Africanized bees replaces their queen at least once a year in the Zona da Mata region. Therefore, it is recommended a constant inspection of the colonies regarding the presence of the queen bee, and the introduction of a new queen when it is absent, if possible with a selected one to be naturally fertilized and, thus, provide a good population for the colony in the peak of the reproductive season in this region—September to December.